Condylar aplasia: a case report - Japatti, Sharanbasappa; Dhoke, Bhavesh; Dhalwale, Georgina; Taneja, Priyanka (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Aplasia of mandibular condyle is one of the several facial manifestations of many syndromes. It is considered as an extremely exceptional stipulation, if it is not seen as a part of any syndrome. The incidence expected 1 in 5600. It occurs due to the growth instability in development of condyle in the intrauterine life, late in the first trimester. It is not discernible at birth and seems to be steadily acquired during the growth. We report a case of condylar aplasia on the right side in an 18-year-old female. The patient reported to the department of Oral and Maxillofacial Surgery at ACPM dental College, Dhule, with a chief complaint of underdeveloped lower jaw. The etiology of this condition was unknown, clinical examination and conventional radiographs revealed complete absence of condyle on the right side. A proper diagnosis along with the differentiation from the syndromic cases is of importance. The aim of this article is to present a case with peculiar type of non-syndromic condylar aplasia.